Late Neolithic to Early-Mid Bronze Age semi-precious stone bead production and consumption at Oakaie and Nyaung'gan in central-northern Myanmar. (March 2021) - Georjon, Cloé; Kyaw, U. Aung Aung; Win, Daw Tin Tin; Win, Daw Thu Thu; Pradier, Baptiste; Willis, Anna; Petchey, Peter; Iizuka, Yoshiyuki; Gonthier, Eric; Pelegrin, Jacques; Bellina, Bérénice; Pryce, T.O.
Abstract: For many decades, the appearance of semi-precious stone ornaments in Mainland Southeast Asian late prehistoric assemblages was closely associated with external actors: Taiwan and Island Southeast Asia in the case of nephrite, and South Asia in the case of carnelian. Carnelian beads in particular have long been held as a type marker of early contact across the Bay of Bengal, from the mid-late 1 st millennium BC. With this paper we demonstrate, from the central-northern Myanmar settlement and cemetery sites of Oakaie and Nyaung'gan, not only the presence of semi-precious stone beads, but also their production during the Late Neolithic to Early-Mid Bronze Age, late 2 nd millennium to early-mid 1 st millennium BC. We employed the chaîne opératoire technique to establish reliable links between the industrial and funerary evidence, as represented by 489 finished beads and a vast quantity of production debris. The sites in question are chronologically-overlapping and separated by only five kilometres, but such ornaments are found across the region and it is of fundamental importance to provide a solid foundation to expand semi-precious stone ornament studies and unravel the complex networks of social interactions that led to their exchange.